Diagnostic Modalities and Current Management Approaches in Retinitis Pigmentosa (RP) - Jaya, Isma Zul Abdillah; Yustiarini, Ima (Vision Science and Eye Health Journal, 2026)
Introduction: Retinitis pigmentosa (RP) is a genetically heterogeneous retinal dystrophy causing progressive vision loss, primarily through rod photoreceptor degeneration. Characterized by nyctalopia and peripheral vision loss progressing to blindness, RP affects ~1 in 4,000 globally, with regional prevalence variations. Despite being a leading cause of inherited blindness, no curative treatments exist; current management focuses on supportive care and emerging therapies like gene therapy. Purpose: This review analyzes RP's clinical features, diagnostic advances, and evolving therapeutic strategies to guide improved patient care. Reviews: RP manifests through progressive photoreceptor degeneration, initially affecting rod cells and later cones, with over 100 identified genetic contributors creating substantial clinical variability. The diagnostic evaluation of RP has advanced significantly through multimodal imaging. While fundoscopy reveals characteristic bone spicules, SD-OCT and fundus autofluorescence (FAF) allow for precise structural assessment of photoreceptor loss. Full-field electroretinography (ffERG) remains the gold standard for detecting early functional deficits. Management strategies have evolved from purely supportive care to mechanism-based treatments. Notable advances include the Argus II retinal prosthesis for end-stage patients and the U.S. FDA-approved gene therapy voretigene neparvovec for RPE65-associated dystrophy. However, challenges persist, particularly the delayed diagnosis due to preserved central vision in early stages and the complexity of addressing high genetic heterogeneity. Conclusions: The diagnosis of RP is established by a combination of clinical examination, multimodal imaging, and electrophysiological testing. While current standard care remains largely supportive, the future of RP management lies in early genetic diagnosis to facilitate personalized gene therapies and stem cell-based regenerative treatments.